The Differentiation of Firm Survival Models in the Poviats of the Zachodniopomorskie Voivodeship - Markowicz, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The aim of the study was to construct models of firms’ survival duration for individual poviats in the Zachodniopomorskie Voivodeship. The first stage was the calculation of the Kaplan‑Meier estimator and the use of a test for the verification of similarities in the survival function for the analysed poviats. As a result, groups of poviats were created. The next stage of research was the construction of duration tables of the studied firms and an analysis of the intensity function of firms’ liquidation for the poviats. The percentage of firms liquidated after two years of activity in different poviats (stage III) was presented. An analysis of correlation between the percentage of firms liquidated in the analysed period and the number of entities registered per 10 thousand of population in the poviats (stage IV) was also conducted. This study used data from the registry of REGON related to companies established in the Zachodniopomorskie Voivodeship in 2009–2011. These entities were observed till the end of 2013. The study results reveal the differentiation of firm survival models in the poviats of the Zachodniopomorskie Voivodeship. Five groups of poviats were distinguished and characterised.